The cellular roles of Ccr4-NOT in model and pathogenic fungi – implications for fungal virulence - Panepinto, John C.; Heinz, Eva; Traven, Ana (Frontiers in Genetics, 2013)
The fungal Ccr4-NOT complex has been implicated in orchestrating gene expression networks that impact on pathways key for virulence in pathogenic species. The activity of Ccr4-NOT regulates cell wall integrity, antifungal drug susceptibility, adaptation to host temperature, and the developmental switches that enable the formation of pathogenic structures, such as filamentous hyphae. Moreover, Ccr4-NOT impacts on DNA repair pathways and genome stability, opening the possibility that this gene regulator could control adaptive responses in pathogens that are driven by chromosomal alterations. Here we provide a synthesis of the cellular roles of the fungal Ccr4-NOT, focusing on pathways important for virulence towards animals. Our review is based on studies in models yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe, and two species that cause serious human infections, Candida albicans and Cryptococcus neoformans. We hypothesize that the activity of Ccr4-NOT could be targeted for future antifungal drug discovery, a proposition supported by the fact that inactivation of the genes encoding subunits of Ccr4-NOT in C. albicans and C. neoformans reduces virulence in a mammalian infection model. We performed bioinformatics analysis to identify similarities and differences between Ccr4-NOT subunits in fungi and animals, and discuss this knowledge in the context of future antifungal strategies.